Modern paradigm formation of advisory services information and consultation activity - Kalna-Dubiniuk, Tatiana; Strashynska, Larysa; Bolotina, Irina; Shapoval, Elena (My University, 2016)
In the article was shown the results of studies on the construction of a new paradigm of advisory services information and consultation activity. The proposed main components of the paradigm of advisory services information and consultation activity, which include: types of modern electronic systems, innovative types of information and consultation technology
Keywords: кафедра маркетингу; globalization; paradigm; information and consulting activity; electronic systems; глобалізація; парадигма; інформаційно-консультаційна діяльність; електронні системи; кафедра економіки праці та менеджменту